Unmet needs and practical solutions in the management of invasive mould infections in Asia. (29th July 2022) - Chen, Yee Chun; Chayakulkeeree, Methee; Chakrabarti, Arunaloke; Gan, Gin Gin; Kwong, Yok Lam; Liu, Wei-Lun; Tan, Ban Hock; Todi, Subhash
Abstract: Management of invasive mould infections (IMIs) is challenging in Asia, as awareness among medical practitioners can be low and resources are limited. Timely diagnosis and appropriate treatment of IMIs can mitigate the impact on morbidity and mortality, but diagnostic methods, as well as access to preferred antifungal medications, may vary throughout the region. Knowledge of local epidemiology and accurate diagnosis and identification of causal pathogens would facilitate optimal treatment but data in Asia are lacking. To address these unmet needs in the management of IMIs, this paper is a call for urgent action in the following areas: improving awareness of the threat of IMIs; providing education to frontline clinicians across a broad range of specialties on 'red flags' for suspicion of IMIs; prioritizing cost-effective rapid diagnostic testing; improving access to preferred antifungal medications; and closing the gaps in local epidemiological data on IMIs to inform local treatment guidelines.